A mycelium cell wall double-component reactive fixed bipolar gradient gel electrolyte, a preparation method thereof and a zinc-iodine battery
Patent Information
- Application Number
- CN202611113197.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-26
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于提供一种菌丝体细胞壁双组分反应性固定的双极梯度凝胶电解质及其制备方法,以解决菌丝体功能组分在凝胶中易迁移、凝胶厚度方向功能均一以及锌碘电池正负极界面需求难以协同匹配的问题
[0010]与仅物理共混菌丝体酶解液的凝胶相比,本发明通过可聚合化实现生物功能组分共价固定,降低浸出;与单一均匀固定电荷凝胶相比,本发明使碘正极侧和锌负极侧分别具有差异化界面化学;与简单双层叠合结构相比,本发明通过部分预聚合和界面共聚形成连续过渡区,降低层间剥离和界面阻抗。
Smart Images

Figure CN122889857A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage and high-value utilization of biomass, specifically relating to a bipolar gradient gel electrolyte obtained by directional fractionation of amino oligosaccharide and dextran from mycelial cell walls, which is covalently fixed in a continuous polymer network after opposite charge fixation and polymerizability, its preparation method, and an aqueous zinc-iodine battery containing the gel electrolyte. Background Technology
[0002] Aqueous zinc-iodine batteries have advantages such as abundant raw materials, high safety, and relatively high theoretical capacity, but the I3 formed during charging and discharging... - I5 - Soluble polyiodide anions tend to migrate from the positive electrode side to the zinc negative electrode side, causing loss of active material, self-discharge, and zinc corrosion. At the same time, the zinc negative electrode also suffers from hydrogen evolution induced by solvation water, local pH changes, and uneven deposition.
[0003] Gel electrolytes can reduce the macroscopic flow of liquid electrolytes and provide mechanical barrier. Existing gel electrolytes typically blend chitosan, alginate, lignin sulfonate, or other natural polymers with synthetic polymers such as polyacrylamide, or utilize natural polymers to form a second network. However, these systems may still suffer from issues such as functional component leaching, conflicting interfacial chemistry between the positive and negative electrodes, and the difficulty in simultaneously controlling both polyiodide anions and Zn by fixing a single charge. 2+ The problem is with the transmission.
[0004] Mycelial cell walls contain β-glucan, chitin / chitosan-like nitrogenous polysaccharides, and proteins. Directly using intact mycelium as a septum, or physically incorporating ungraded mycelial enzymatic hydrolysate into the gel, makes it difficult to control the spatial positions of different functional components; low-molecular-weight enzymatic hydrolysates may also migrate from highly hydrated gels. Therefore, a technical solution is needed that can directionally separate different components of the mycelial cell wall, assign them opposite fixed charges, and covalently fix them in a gel network. Summary of the Invention
[0005] The purpose of this invention is to provide a bipolar gradient gel electrolyte with two components of mycelial cell wall reactive immobilization and its preparation method, in order to solve the problems of easy migration of mycelial functional components in the gel, uniform function in the gel thickness direction, and difficulty in coordinating and matching the positive and negative electrode interfaces of zinc-iodine batteries.
[0006] To achieve the above objectives, the present invention first performs sequential graded enzymatic hydrolysis of the mycelial cell wall: firstly, the outer layer or matrix layer of the cell wall is deconstructed with β-glucanase and protease to obtain a glucan-enriched fraction, and then the solid residue is treated with chitin deacetylase and chitosanase and / or chitinase to obtain an amino oligosaccharide-enriched fraction.
[0007] The amino oligosaccharide enriched fraction is permanently cationized and polymerizable unsaturated groups are introduced to obtain cationic reactive biomolecules; the dextran enriched fraction is carboxylated or phosphorylated and polymerizable unsaturated groups are introduced to obtain anionic reactive biomolecules.
[0008] Cationic reactive biomacromolecules and anionic reactive biomacromolecules were added to the iodine-positive and zinc-negative electrode precursor solutions in different proportions. Through sequential laying, partial prepolymerization, interfacial interdiffusion, and overall copolymerization, the fixed charge in the gel thickness direction was continuously transitioned from the positive fixed charge on the iodine-positive electrode side to the negative fixed charge on the zinc-negative electrode side, and both types of mycelium-derived biomacromolecules were covalently linked to the polymer network.
[0009] The cation immobilization group on the iodine positive electrode side is used for multi-site binding and confinement of polyiodine anions; the anion and hydroxyl sites on the zinc negative electrode side are used to regulate Zn 2+ The solubilization and interfacial ion flux generate electrostatic repulsion against polyiodine anions; the reverse gradient of positive and negative fixed charges creates a directional ion-selective environment inside the gel, thereby reducing the net migration of polyiodine species to the zinc anode side.
[0010] Compared to gels made solely from physically blended mycelial hydrolysates, this invention achieves covalent fixation of biofunctional components through polymerizability, reducing leaching; compared to gels with a single uniformly fixed charge, this invention creates differentiated interfacial chemistry on the iodine positive electrode side and the zinc negative electrode side; compared to simple bilayer stacked structures, this invention forms a continuous transition region through partial prepolymerization and interfacial copolymerization, reducing interlayer delamination and interfacial impedance. Attached Figure Description
[0011] Figure 1 This is a schematic diagram of the mycelial cell wall sequential grading, dual-reactivity modification, and bipolar gradient gel preparation process of the present invention.
[0012] Figure 2 This is a schematic diagram of the cross-sectional structure of the bipolar fixed charge gradient gel of the present invention.
[0013] Figure 3 This is a schematic diagram of the structure and ion regulation of an aqueous zinc-iodine battery using the gel electrolyte of this invention.
[0014] Figure 4 A schematic diagram showing the sequential laying, partial prepolymerization, and interfacial copolymerization of two gel precursor solutions. Detailed Implementation
[0015] The following embodiments are used to illustrate the technical concept of the present invention. Unless otherwise stated, all percentage contents are mass percentages, enzyme dosage is based on the dry weight of mycelium, degree of substitution of polymerizable groups is expressed as the number of moles of unsaturated groups introduced per 100 monosaccharide repeating units, and fixed charge capacity is expressed as the number of millimoles of titratable fixed charge contained in each gram of dried functional component.
[0016] I. Testing and Characterization Methods
[0017] The monosaccharide and oligosaccharide compositions of the amino oligosaccharide-enriched fraction and the dextran-enriched fraction were determined by high-performance liquid chromatography (HPLC) or high-performance anion exchange chromatography-pulse amperometric detection (HPLC-PAC). Weight-average molecular weight and molecular weight distribution were determined by size exclusion chromatography (MSC). Amino capacity, quaternary ammonium capacity, and carboxyl capacity were determined by acid-base titration or polyelectrolyte titration, respectively. The introduction of polymerizable unsaturated groups was characterized by nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared spectroscopy (FTIR), and the degree of substitution was calculated accordingly.
[0018] The C-FMO and A-FMO distributions along the gel thickness were determined using cross-sectional X-ray photoelectron spectroscopy, time-of-flight secondary ion mass spectrometry, or micro-area Raman spectroscopy. The zeta potentials of the gel surfaces in low-ionic-strength media were measured, and combined with the fixed charge capacity measurements of the samples on both sides, it was determined whether a fixed charge sign reversal and continuous composition transition occurred along the gel thickness.
[0019] The degree of functional component fixation was evaluated by leaching test: a gel of specified mass and size was placed in a zinc salt solution of the same type and concentration as the battery electrolyte salt, soaked at a specified temperature, and sampled at a predetermined time; the total organic carbon, amino sugar and dextran content in the soaking solution was determined, and the cumulative leaching rate of C-FMO and A-FMO was calculated based on the initial functional component content of the gel.
[0020] Multiiodine species migration was determined using an H-type diffusion cell combined with UV-Vis absorption spectroscopy. The zinc anode interface performance was evaluated using Zn||Zn symmetric cell cycling, Zn||Cu deposition / stripping coulombic efficiency, hydrogen evolution, corrosion, electrochemical impedance, zinc deposition morphology, and crystal orientation. Zinc-iodine full cell tests recorded iodine loading, zinc anode areal capacity or excess coefficient, electrolyte content per unit area, cutoff voltage, current density, test temperature, and number of parallel samples.
[0021] II. Mycelial Raw Materials and Pretreatment
[0022] The mycelium can be edible fungi, medicinal fungi, or industrial fungi mycelium obtained through liquid fermentation, or it can be waste mycelium generated during enzyme preparations, organic acids, antibiotics, or food fermentation processes. Preferred strains include one or more of Aspergillus niger, Aspergillus oryzae, Pleurotus ostreatus, Lentinus edodes, Ganoderma lucidum, Hericium erinaceus, and Grifola frondosa.
[0023] The mycelium is washed with water until the conductivity of the washing solution is stable. Further washing with a 20%-70% ethanol aqueous solution can be used to remove lipid-soluble metabolites. After vacuum drying or freeze-drying at 40-80℃, it is pulverized to 60-200 mesh. The preferred mass-to-volume ratio of mycelium powder to buffer solution is 1:(8-40) g / mL.
[0024] III. Sequential graded enzymatic hydrolysis
[0025] The first stage is the outer layer deconstruction stage. Mycelial powder is dispersed in acetate, citrate, or phosphate buffer at pH 4.5-6.5, and β-1,3-glucanase and protease are added; β-1,6-glucanase, mannanase, or α-1,3-glucanase may be further added. The total β-glucanase activity is preferably 50-1500 U / g, and the protease activity is preferably 20-800 U / g. The reaction is carried out at 35-55℃ for 2-16 h.
[0026] After the first stage, centrifuge at 3000-10000 g for 5-30 min or use microfiltration to separate the fractions. Collect the supernatant as the crude dextran enrichment fraction and retain the solid residue. The crude dextran enrichment fraction can be fractionated by ultrafiltration membrane with a cutoff range of 0.3-30 kDa, preferably retaining the 0.5-20 kDa fraction, and the content of inorganic salts and free monosaccharides can be reduced by dialysis or nanofiltration.
[0027] The second stage is the nitrogen-containing polysaccharide conversion stage. The solid residue obtained in the first stage is resuspended in a pH 5.0-8.0 buffer solution, and chitin deacetylase, chitosanase and / or chitinase are added. The activity of chitin deacetylase is preferably 20-800 U / g, and the total activity of chitosanase and chitinase is preferably 50-1500 U / g. The reaction is carried out at 35-55℃ for 4-30 h.
[0028] After the second stage, solid-liquid separation is performed, and the resulting supernatant is the crude fraction enriched with amino oligosaccharides. This crude fraction can be fractionated by ultrafiltration at 0.3-30 kDa, preferably retaining the 0.5-15 kDa fraction. The free and protonable amino capacity of the amino oligosaccharide enriched fraction is preferably 0.5-4.0 mmol / g dry matter, and the weight-average molecular weight is preferably 0.5-15 kDa; the β-glucan content of the dextran enriched fraction is preferably 40%-95% of its dry matter, and the amino capacity is less than 0.3 mmol / g.
[0029] Both stages of enzymatic hydrolysis can be completed by incubating at 75-95℃ for 5-30 min after the reaction, or by removing the enzyme protein through ultrafiltration. The fraction can be used directly as a concentrated solution or stored after freeze-drying.
[0030] IV. Preparation of cationic reactive biomacromolecules
[0031] The amino oligosaccharide enrichment fraction was dissolved in water and permanently cationized using glycidyltrimethylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, or an epoxy compound containing a quaternary ammonium group. The preferred reaction pH was 8.0-11.5, the temperature was 35-75℃, and the reaction time was 1-16 h, so that the quaternary ammonium group capacity reached 0.15-2.5 mmol / g.
[0032] Subsequently, carbon-carbon double bonds are introduced using methacrylic anhydride, glycidyl methacrylate, acrylic anhydride, or polymerizable compounds containing isocyanate groups. The reaction is preferably carried out at pH 7.5-10.5 and 10-45°C for 1-12 h to achieve a degree of substitution of 1%-30% for the polymerizable groups. The reaction product is purified by dialysis, ultrafiltration, or precipitation to obtain a cationic reactive biomacromolecule, denoted as C-FMO.
[0033] V. Preparation of Anionic Reactive Biomolecules
[0034] The dextran-enriched fraction is then carboxylated or phosphorylated. Carboxylation can be performed using a TEMPO / halide / hypohalate system to oxidize some primary hydroxyl groups to carboxyl groups, or by carboxymethylation. Phosphorylation can be performed using sodium trimetaphosphate, a phosphate-urea system, or other reagents capable of introducing phosphate groups onto the polysaccharide hydroxyl groups. The preferred anionic fixed charge capacity is 0.15-2.5 mmol / g.
[0035] The dextran fraction after anionization is further treated with methacrylic anhydride, glycidyl methacrylate or acrylic anhydride to introduce polymerizable unsaturated groups, so that the degree of substitution is 1%-30%, to obtain anionic reactive biomacromolecules, denoted as A-FMO.
[0036] VI. Preparation of dual precursor solutions and bipolar gradient gels
[0037] The iodine cathode-side precursor solution comprises C-FMO, A-FMO, hydrophilic vinyl monomers, crosslinking agents, an initiation system, zinc salt, and water, wherein the dry matter mass ratio of C-FMO to A-FMO is not less than 3:1, preferably 4:1-20:1. The zinc anode-side precursor solution comprises the same type of components, but the dry matter mass ratio of C-FMO to A-FMO is not more than 1:3, preferably 1:4-1:20.
[0038] The hydrophilic vinyl monomer may be selected from one or more of acrylamide, N-hydroxyethylacrylamide, N,N-dimethylacrylamide, hydroxyethyl acrylate, polyethylene glycol diacrylate, and 2-hydroxyethyl methacrylate. The mass fraction of the hydrophilic vinyl monomer in the precursor solution is preferably 4%-25%, and the total amount of C-FMO and A-FMO is preferably 0.5%-15% of the precursor solution mass.
[0039] The crosslinking agent can be selected from N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, or a multifunctional vinyl crosslinking agent, and its amount is preferably 0.01%-1.0% of the total mass of the vinyl monomers. The zinc salt can be selected from one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, zinc acetate, and zinc iodide, and the total concentration is preferably 0.5-3.5 mol / L.
[0040] A low-temperature redox initiation system is preferred, including persulfate / bisulfite, persulfate / tetramethylethylenediamine, hydrogen peroxide / ascorbic acid, or other systems capable of initiating polymerization at 0-35°C; visible light or ultraviolet light initiation can also be used. The total amount of initiator is preferably 0.01%-2% of the total mass of vinyl monomers.
[0041] The iodine-positive-side precursor solution is added to a mold or porous support, making it account for 20%-60% of the final gel thickness. When the polymerization conversion reaches 5%-45%, the zinc-negative-side precursor solution is added. The two precursor solutions are allowed to interdiffusion at the interface for 5 s-30 min, and then the overall polymerization is completed. This forms a gel with C-FMO-rich iodine-positive-side, A-FMO-rich zinc-negative-side, and a continuous transition zone in between.
[0042] The continuous transition region preferably accounts for 3%-35% of the total gel thickness. The total gel thickness is preferably 50-1500 μm, and the water content is preferably 25%-90%. The dry-based positive fixed charge capacity on the iodine positive electrode side, as determined by polyelectrolyte titration, is preferably 0.05-1.8 mmol / g, and the dry-based negative fixed charge capacity on the zinc negative electrode side is preferably 0.05-1.8 mmol / g.
[0043] In C-FMO and A-FMO, the polymerizable groups copolymerize with hydrophilic vinyl monomers during polymerization, thus linking the two types of mycelium-derived biomacromolecules to a continuous polymer network via covalent bonds. The degree of immobilization can be evaluated using immersion leaching tests in zinc salt solution.
[0044] VII. Zinc-Iodine Batteries
[0045] The bipolar gradient gel is placed between an iodine-based positive electrode and a zinc-based negative electrode, with the cation-reactive biomacromolecule enrichment surface facing the iodine-based positive electrode and the anion-reactive biomacromolecule enrichment surface facing the zinc-based negative electrode. The iodine-based positive electrode can be an I2 / porous carbon composite positive electrode, a polyiodide positive electrode, or an iodine-containing organic positive electrode; the zinc-based negative electrode can be zinc foil, zinc powder coating, zinc alloy, or a three-dimensional zinc substrate.
[0046] The gel can be pre-formed in a mold and then assembled, or it can be first formed into a gradient gel in a porous inert support and then assembled. For in-situ polymerization within the battery, it is preferable to use low-temperature initiation at 0-30°C, and to locally consume the oxidizing initiator in the precursor solution before it comes into contact with the zinc anode, or to use an isolated infusion method, in order to reduce side reactions.
[0047] Example 1: Preparation of two fractions from Aspergillus niger mycelium
[0048] 100 g of waste mycelium from Aspergillus niger fermentation was washed three times with deionized water, vacuum dried at 60℃, and then pulverized through a 100-mesh sieve. 10 g of the mycelium powder was dispersed in 200 mL of pH 5.5 acetate buffer, and 500 U / g of β-1,3-glucanase and 200 U / g of neutral protease were added. The mixture was stirred at 45℃ for 8 h. After centrifugation, the supernatant was collected, and the solid residue was retained.
[0049] The supernatant was sequentially treated with 10 kDa and 0.5 kDa ultrafiltration membranes, and the dextran-enriched fraction with a cutoff of 0.5–10 kDa was collected. The solid residue was resuspended in 150 mL of pH 6.5 phosphate buffer, and 200 U / g chitin deacetase and 400 U / g chitosanase were added. The mixture was reacted at 42 °C for 12 h. The supernatant was collected by centrifugation and fractionated by 0.5–10 kDa ultrafiltration to obtain the amino oligosaccharide-enriched fraction.
[0050] Example 2: Preparation of C-FMO
[0051] The amino oligosaccharide enrichment fraction from Example 1 was dissolved in 100 mL of water at a dry weight of 5 g. The pH was adjusted to 10.0 with sodium hydroxide, and glycidyltrimethylammonium chloride was added to achieve a molar ratio of 0.35:1 to the titratable amino group. The reaction was carried out at 55 °C for 6 h. After dialyzing the reaction solution with 3 kDa, the pH was adjusted to 8.5. Methacrylic anhydride was added dropwise under ice bath conditions to achieve a molar ratio of 0.12:1 to the monosaccharide repeating unit. The reaction was then carried out at 25 °C for 4 h, dialyzed, and freeze-dried to obtain C-FMO.
[0052] Example 3: Preparation of A-FMO
[0053] The dextran enrichment fraction from Example 1 was dissolved in 250 mL of water at a dry weight of 5 g. 0.08 g of TEMPO and 0.5 g of sodium bromide were added. Sodium hypochlorite was added dropwise at 5°C and pH 10.0 to achieve a molar ratio of 0.15:1 to the glucose repeating unit. The reaction was terminated with ethanol, and dialyzed to obtain carboxylated dextran. This carboxylated dextran was reacted with methacrylic anhydride at pH 8.5 and 20°C for 4 h, dialyzed, and freeze-dried to obtain A-FMO.
[0054] Example 4: Preparation of bipolar gradient gel
[0055] Prepare the iodine-side precursor solution: C-FMO 4.0 g, A-FMO 0.5 g, acrylamide 12 g, N-hydroxyethylacrylamide 3 g, N,N'-methylenebisacrylamide 0.03 g, add 2 mol / L zinc sulfate solution to a total mass of 100 g. Prepare the zinc-side precursor solution: C-FMO 0.5 g, A-FMO 4.0 g, the concentrations of the remaining monomers, crosslinking agents, and zinc salts are the same as those in the iodine-side precursor solution.
[0056] Both precursor solutions were deoxygenated and then added to an ammonium persulfate / sodium bisulfite redox initiation system. The iodine positive electrode side precursor solution was first injected into a mold with a thickness of 400 μm to a height of approximately 180 μm, and prepolymerized at 15 °C until a pregel that could maintain its shape but still had a fluid surface was formed. Subsequently, the zinc negative electrode side precursor solution was added to a total thickness of 400 μm, and after standing for 2 min, polymerization was completed at 20 °C.
[0057] Example 5: Gels with different gradient ratios
[0058] The gel was prepared according to Example 4. The C-FMO:A-FMO mass ratio in the iodine positive electrode precursor solution was set to 4:1, 8:1 and 12:1, respectively, and the C-FMO:A-FMO mass ratio in the zinc negative electrode precursor solution was set to 1:4, 1:8 and 1:12, respectively. The thickness ratio of the first layer was set to 30%, 45% and 60%, respectively, to screen the equilibrium range of fixed charge gradient, ionic conductivity and mechanical integrity.
[0059] Comparative Example 1: Uniform gelation of non-covalent crude enzymatic hydrolysate
[0060] A mixed enzymatic hydrolysate of mycelium that was not ultrafiltered, fractionated, cationized / anionized, or polymerizable was added to an acrylamide precursor solution in the same amount as the total dry matter of C-FMO and A-FMO in Example 4 to prepare a homogeneous physical blend gel for evaluating the leaching of functional components and the role of gradient structures.
[0061] Comparative Example 2: Homogeneous gel with fixed covalent groups but no gradient
[0062] C-FMO and A-FMO were uniformly added to all the precursor liquid at a 1:1 mass ratio and polymerized in a single casting. Other conditions were the same as in Example 4. This was used to evaluate the effect of a fixed charge reversal gradient on a uniform two-component network.
[0063] Comparative Example 3: Unilateral Functional Gel
[0064] Single fixed-charge gels were prepared using only C-FMO or only A-FMO, with other conditions the same as in Example 4, to distinguish between the multi-iodine confinement effect and the zinc anode regulation effect.
[0065] The above embodiments are used to illustrate the technical concept of the present invention, and the amount of raw materials, reaction conditions, and structural parameters can be adjusted within the scope defined by the present invention. The core of the present invention lies in: obtaining two types of cell wall fractions with different compositions from the same mycelial raw material; respectively endowing them with opposite fixed charges and polymerizable groups; forming a continuous gradient with reversed fixed charge signs in the gel thickness direction; and covalently fixing the two types of fractions to the same continuous polymer network.
Claims
1. A method for preparing a bipolar gradient gel electrolyte with two-component reactive immobilization of mycelial cell walls, characterized in that, include: (1) After pretreatment of the mycelial raw material, the first stage of enzymatic hydrolysis is carried out by β-glucanase and protease, and solid-liquid separation is obtained to obtain glucan-enriched fraction and solid residue; then the solid residue is enzymatically hydrolyzed by chitin deacetase and chitosanase and / or chitinase, and solid-liquid separation is obtained to obtain amino oligosaccharide-enriched fraction. (2) Introduce permanent cationic groups and polymerizable unsaturated groups into the enriched fraction of the amino oligosaccharide to obtain the cationic reactive biomacromolecule C-FMO; Introduce anionic groups and polymerizable unsaturated groups into the enriched fraction of the dextran to obtain the anionic reactive biomacromolecule A-FMO; (3) Prepare iodine positive electrode side precursor solution and zinc negative electrode side precursor solution respectively. Both precursor solutions contain C-FMO, A-FMO, hydrophilic vinyl monomer, crosslinking agent, initiation system, zinc salt and water. The dry matter mass ratio of C-FMO to A-FMO in the iodine positive electrode side precursor solution is not less than 3:1, and the dry matter mass ratio of C-FMO to A-FMO in the zinc negative electrode side precursor solution is not more than 1:
3. (4) The iodine positive electrode side precursor liquid and the zinc negative electrode side precursor liquid are laid in sequence. When the first-laid precursor liquid is in a partially prepolymerized state, the second precursor liquid is laid, so that the two precursor liquids can diffuse into each other at the interface and complete copolymerization to form a gel electrolyte with a continuous composition transition zone. The C-FMO and A-FMO are covalently linked to the same continuous polymer network through their respective polymerizable unsaturated groups, and the gel electrolyte has a positive fixed charge on the iodine positive electrode side and a negative fixed charge on the zinc negative electrode side.
2. The preparation method according to claim 1, characterized in that, The mycelial raw material is derived from one or more of Aspergillus niger, Aspergillus oryzae, Pleurotus ostreatus, Lentinus edodes, Ganoderma lucidum, Hericium erinaceus, or Grifola frondosa. The first stage of enzymatic hydrolysis uses β-1,3-glucanase, and optionally β-1,6-glucanase, mannanase, or α-1,3-glucanase. The pH of the first stage of enzymatic hydrolysis is 4.5-6.5, the temperature is 35-55℃, and the time is 2-16 h. The pH of the second stage of enzymatic hydrolysis is 5.0-8.0, the temperature is 35-55℃, and the time is 4-30 h. The weight-average molecular weight of the amino oligosaccharide enriched fraction is 0.5-15 kDa and the amino capacity is 0.5-4.0 mmol / g dry matter. The β-glucan content of the dextran enriched fraction is 40%-95% of its dry matter and the amino capacity is less than 0.3 mmol / g.
3. The preparation method according to claim 1 or 2, characterized in that, The permanent cationic group is a quaternary ammonium group and / or an imidazolium group, and the anionic group is a carboxyl group, a phosphate group, and / or a sulfonate group; the positive fixed charge capacity of the C-FMO is 0.15-2.5 mmol / g dry matter, the negative fixed charge capacity of the A-FMO is 0.15-2.5 mmol / g dry matter, and the degree of substitution of the polymerizable unsaturated groups of the C-FMO and A-FMO is independently 1%-30%.
4. The preparation method according to any one of claims 1-3, characterized in that, The hydrophilic vinyl monomer is selected from one or more of acrylamide, N-hydroxyethylacrylamide, N,N-dimethylacrylamide, hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and polyethylene glycol diacrylate; the polymerization is carried out at 0-35°C via a redox initiation system; the continuous composition transition region accounts for 3%-35% of the total gel thickness, the iodine positive electrode side region accounts for 20%-60% of the total gel thickness, and the total gel thickness is 50-1500 μm.
5. A bipolar gradient gel electrolyte with two-component reactive immobilization of mycelial cell walls, characterized in that, It includes a continuous covalent polymer network formed of hydrophilic vinyl monomers, a C-FMO covalently connected to the continuous covalent polymer network, and an A-FMO covalently connected to the continuous covalent polymer network; The C-FMO is obtained by permanent cationization and polymerizability of the amino oligosaccharide enrichment fraction of mycelial cell wall, and the A-FMO is obtained by anionization and polymerizability of the dextran enrichment fraction of the same mycelial raw material; the C-FMO is enriched on the first surface side of the gel, and the A-FMO is enriched on the second surface side opposite to the first surface, and the composition of C-FMO and A-FMO changes continuously between the first surface and the second surface, so that the first surface side has a positive fixed charge and the second surface side has a negative fixed charge.
6. The bipolar gradient gel electrolyte according to claim 5, characterized in that, Based on the dry gel, the positive fixed charge capacity on the first surface side is 0.05-1.8 mmol / g, and the negative fixed charge capacity on the second surface side is 0.05-1.8 mmol / g; the gel electrolyte contains 0.5-3.5 mol / L of zinc salt, has a water content of 25%-90%, and a thickness of 50-1500 μm.
7. The bipolar gradient gel electrolyte according to claim 5 or 6, characterized in that, After the gel electrolyte is soaked in an aqueous solution of the same zinc salt as the zinc salt it contains for 7 days, the total leaching mass of C-FMO and A-FMO is no more than 10% of the initial total mass of C-FMO and A-FMO.
8. An aqueous zinc-iodine battery, comprising an iodine-based positive electrode, a zinc-based negative electrode, and a bipolar gradient gel electrolyte as described in any one of claims 5-7 disposed between the iodine-based positive electrode and the zinc-based negative electrode, characterized in that... The first surface of the bipolar gradient gel electrolyte faces the iodine-based positive electrode, and the second surface faces the zinc-based negative electrode.
9. The aqueous zinc-iodine battery according to claim 8, characterized in that, The iodine-based positive electrode is an I2 / porous carbon composite positive electrode, a polyiodide positive electrode, or an iodine-containing organic positive electrode, and the zinc-based negative electrode is a zinc foil, a zinc powder coating, a zinc alloy, or a three-dimensional zinc matrix.
10. The aqueous zinc-iodine battery according to claim 8 or 9, characterized in that, The zinc salt is one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, zinc acetate, and zinc iodide.